THE EFFECTIVENESS OF VALUES CLARIFICATION GROUP COUNSELING TO MINIMIZE STUDENT BULLYING BEHAVIOR IN SCHOOLS - I Made Sonny Gunawan; Sri Sukarni; Reza Zulaifi; Ichwanul Mustakim (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
The purpose of this study was to emphasize the effect of values clarification group counseling in minimizing bullying behavior by students at school. This study used a one group pretest-posttest control design experimental approach. The subjects in this study were 12 students of SMA Negeri 3 Mataram, Indonesia. Data were collected using the European Bullying Intervention Project Questionnaire (BIPQ) which was adapted according to the characteristics of the research subjects. Data analysis used one way ANOVA statistic. The research results show that values clarification group counseling is effective in minimizing student bullying behavior. The changes that occur in students after receiving treatment are that students become more able to respect their friends, have a high attitude of respect, and care more about the environment around them.